The Venetic inscriptions from Idrija pri Bači revisited - Luka Repanšek (Arheološki Vestnik, 2025)
The article offers a thorough palaeographical analysis of the three Venetic inscriptions from Idrija pri Bači (Is 1, Is 2, and Is 3), based on the renewed autopsy of the sources in the Prähistorische Abteilung of the Naturhistorisches Museum in Vienna. Given the significant discrepancies in the existing drawings and transcriptions of the three inscriptions, the gap for a much-needed authoritative reading of Is 1 and Is 2 is now filled, as is the need for a reinterpretation of the still existing dilemmas in relation to several significant palaeographic peculiarities of the three inscriptions.